Apical periodontitis induces changes on oxidative stress parameters and increases Na+/K+-ATPase activity in adult rats. (October 2020) - Barcelos, Raquel Cristine Silva; Rosa, Higor Zuquetto; Roversi, Karine; Tibúrcio-Machado, Camilla dos Santos; Inchaki, Paula Tassoni; Burger, Marilise Escobar; Bier, Carlos Alexandre de Souza
Highlights: Apical periodontitis (AP) was induced by pulp occlusal exposure in rats. AP favored oxidative damages development in rats' peripheral organs. AP was related to increased Na + K + -ATPase activity in heart, liver and pancreas. AP modulated the endogenous antioxidant defense. Cell electrochemical changes may be involved in the AP pathogenesis. Abstract: Objectives: Endodontic infection can cause systemic alterations. The involvement of oxidative stress (OS) and transmembrane enzymes compose the pathogenesis of various systemic diseases. However, the relation among apical periodontitis (AP), OS parameters, and Na + /K + -ATPase (NKA) pump was not reported in the literature. This study evaluated the AP influence on OS parameters and NKA activity in adult rats. Methods: Adult male Wistar rats (sixteen weeks old) were randomly assigned to two experimental groups: control (CT group; n = 8) and AP (AP group; n = 9), which was induced in the first right mandibular molar tooth. After 21 days of AP induction, mandibles were dissected for radiographic analysis. In addition, the heart, liver, pancreas, and kidney were collected for analysis of endogenous OS parameters and NKA activity. Data were analyzed by Student's T-test. Values of p < 0.05 were considered statistically significant. Results: AP presence increased reactive species (RS) generation only in the heart, while the other analyzed organs did not have this parameter modified. Heart and pancreas had a decreased endogenous antioxidant system (catalase activity and vitamin C levels), liver and kidney had an increased one. AP increased NKA activity in the heart, liver, and pancreas, but not in the kidney. Conclusion: The modulation of both endogenous antioxidant defense system and NKA activity in vital organs suggested that alterations in the antioxidant status and cellular electrochemical gradient may be involved in the AP pathophysiology.